Experimental Velogenic Newcastle Disease Can Be Very Severe and Viscerotropic in Chickens but Moderate and Neurotropic in Guinea Fowls - Igwe, O. Amarachukwu; Ezema, S. Wilfred; Eze, C. Didacus; Okoye , O.A. John (International Journal of Poultry Science, 2014)
Information about the pathogenesis of Newcastle disease (ND) is still limited in many avian species including some poultry birds. Four weeks old cockerels and guinea fowls were inoculated with a local Nigerian velogenic ND (VND) Virus (VNDV) strain, Kudu-113, intramuscularly. The main clinical signs in chickens were severe depression and diarrhoea while the guinea fowls showed mainly leg paralysis. Weight loss was significant in the infected birds in both species from days 3-21 post inoculation (PI). The total mortalities in the guinea fowls and chickens were 22.2 and 94.6%, respectively. The guinea fowls showed no proventricular haemorrhage, intestinal ulcers, haemorrhages and swelling of the caecal tonsil which were all prominent in the cockerels. Gross congestion of the brain was observed in the guinea fowls only. But lesions in the lymphoid organs and microscopic changes in the brain were similar in both species. The antibody response to the viral inoculation was higher in the chickens than the guinea fowls. The above observations confirm experimentally that chickens are more susceptible to VND than guinea fowls. Furthermore, the Kudu-113 infection was viscerotropic in chickens but neurotropic in guinea fowls.